Debi Sintia (2018). IMPLEMENTASI MODIFIKASI PEMBELAJARAN AKTIVITAS PERMAINAN BOLA VOLI UNTUK MENGEMBANGKAN WAKTU AKTIF BELAJAR - Debi Sintia, - (2018)
Penelitianinibertujuanuntukmemperbaikidanmeningkatkankualitaspembelajaranaktivitaspermainan bola volipadamatapelajaranPendidikanJasmaniOlahragadanKesehatan (PJOK), khususnyauntukmengembangkanwaktuaktivitasbelajarsiswa.SuatumetodePenelitianTindakanKelas (PTK) yang terdiriatasduasiklusdilakukanuntukmenerapkanimplementasimodifikasipembelajaranaktivitaspermainan bola voliuntukmengembangkanwaktuaktifbelajar.Sikluspenelitiandilakukanmelaluiempattahapan, yaitu: perencanaan, pelaksanaan, observasidanrefleksi, denganmasing-masingsiklusterdiriatasduatindakan. Subjekpenelitianadalahsiswakelas VIII B di SMP Negeri 6 Cimahi.Teknikpengumpulan data yang dilakukandalampenelitianiniadalahobservasi, catatanlapangan, catatan observer, catatanhasildiskusidan format WaktuAktifBelajar (WAB). Teknikanalisis data untuk data kualitatifdilakukandenganmendeskripsikanpelaksanaantindakanmelaluicatatanlapangan, catatan observer, dancatatanhasildiskusi.Sedangkanteknikanalisis data kuantitatifdilakukandenganmenghitungprosentasejumlahwaktuaktifbelajar.Hasilrekapitulasipeningkatanwaktuaktifbelajarsiswaadalahsebagaiberikut: padasiklus I tindakan I jumlahwaktuaktivitasbelajarsiswasebesar 48,33%, siklus I tindakan II jumlahwaktuaktivitasbelajarsiswasebesar 51,67%, siklus II tindakan I jumlahwaktuaktifbelajarsiswasebesar 55%, siklus II tindakan II jumlahwaktuaktifbelajarsiswasebesar 60%. Berdasarkanperkembanganhasilbelajartersebut, makadapatdisimpulkanbahwamodifikasipembelajaranaktivitaspermainan bola volidapatmengembangkanwaktuaktivitasbelajarsiswa. ;---This research aims to fix and improve the quality of learning the game of volleyball activities on subjects of physical education sport and health, in particular to develop time learning activities of students. A Classroom Action Research Method (PTK) consisting of two cycles was carried out to apply modification of volleyball game activity learning to develop time learning activities. The research cycle is done through four stages, namely: planning, implementation, observation and reflection, with each cycle comprising two acts. The subject of this research is students of class VIII B in6 Junior High School, Cimahi. The technique of data collection conducted in this research is the observation, field notes, notes observer, notes the results of the discussion and Active Learning Time format . Data analysis techniques for qualitative data is done by describing the implementation of the action through the field notes, the observer notes, and the results of the discussion notes. While quantitative data analysis techniques was conducted by calculating the percentage of the amount of active learning time. The results of the recapitulation of the increased active learning time students are as follows: in cycle I, Act I the amount of time learning activities of students of 48.33%, cycle I Act II the amount of active learning time students of 51.67%, cycle II action I amount active student learning time of 55%, cycle II Action II the number of active student learning time of 60%. Based on the development of the learning results, it can be concluded that the modifications to the learning activities of volleyball game can develop time learning activities of students.